Impact of Performance Appraisals on Employee Performance in Private Universities and Institutes of Afghanistan - Stanikzai, Irfan Ullah; Jawad, Khushal; Lawraand, Habib Ullah (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
This study investigates the impact of performance appraisals on employee performance in private Universities and Institutes of Afghanistan. The research aims to address the lukewarm attitudes towards the performance appraisal system, which can negatively affect organizational productivity. A sample of 250 respondents from private universities and higher education institutes in Afghanistan was selected using a simple random sampling technique. Data was collected through a structured questionnaire and analyzed. The findings indicate a high level of awareness of performance appraisal among staff in private universities and institutes. The study also reveals that performance appraisal significantly impacts employee performance. However, a challenge identified is the inability to provide timely feedback within the performance appraisal system. As a recommendation, the study suggests that management should maintain objectivity during the appraisal process, provide regular feedback, and offer career development opportunities to gain a competitive advantage in the organization